Treatment-related adverse events of PD-1 and PD-L1 inhibitor-based combination therapies in clinical trials: a systematic review and meta-analysis. Issue 9 (September 2021) - Zhou, Xiaoxiang; Yao, Zhuoran; Bai, Hua; Duan, Jianchun; Wang, Zhijie; Wang, Xin; Zhang, Xue; Xu, Jiachen; Fei, Kailun; Zhang, Zhen; Tan, Fengwei; Xue, Qi; et al.
Summary: Background: Numerous ongoing trials are testing anti-PD-1-based or anti-PD-L1-based cancer treatment combinations. Understanding the toxicity profiles of treatment-related adverse events is essential. The aim of this study was to comprehensively investigate the incidences and profiles of treatment-related adverse events across different combination therapies. Methods: We did a systematic review and meta-analysis comparing different chemotherapy, targeted therapy, immunotherapy, and radiotherapy combinations with PD-1 or PD-L1 inhibitors. We searched Pubmed, Embase, and Cochrane databases for articles published in English between Jan 1, 2000, and May 21, 2020, investigating globally approved PD-1 or PD-L1 inhibitor-based combination therapies. Only prospective trials reporting overall incidence or tabulated data of treatment-related adverse events were included. Trials investigating sequential therapies, comprising three or more classes of therapies, and enrolling less than ten patients were excluded. The primary outcomes were overall incidences and profiles for all-grade and grade 3 or higher treatment-related adverse events by random-effect models. Heterogeneity between studies was assessed with I 2 statistics. The summary measures for main outcomes are incidences (95% CI). The 95% CI were calculated together with the incidence through a random-effects model with a logit transformation. The protocol is registered with PROSPERO (CRD42020189617). Findings: We identified 2540 records, of which 161 studies (17 197 patients) met the inclusion criteria. The overall incidence of treatment-related adverse events in the chemotherapy combination was 97·7% (95% CI 96·4–98·5; I 2 =75%) for all-grade adverse events and 68·3% (60·7–75·0; I 2 =93%) for grade 3 or higher adverse events; in the targeted therapy combination was 94·5% (90·7–96·8; I 2 =86%) for all-grade adverse events and 47·3% (37·3–57·5; I 2 =93%) for grade 3 or higher adverse events; in the immunotherapy combination was 86·8% (80·9–91·1; I 2 =94%) for all-grade adverse events and 35·9% (29·5–42·9; I 2 =92%) for grade 3 or higher adverse events; and in the radiotherapy combination was 89·4% (69·0–96·9; I 2 =74%) for all-grade adverse events and 12·4% (4·4–30·6; I 2 =73%) for grade 3 or higher adverse events. For these four combination therapies, the most common all-grade adverse events were anaemia (45.4% [95% CI 32·4–59·1]), fatigue (34·3% [27·5–41·9]), fatigue (26·4% [19·2–35·2]), and dysphagia (30·0% [18·7–44·5]), respectively, and the most common grade 3 or higher adverse events were neutropenia (19·6% [13·5–27·7]), hypertension (9·3% [5·7–14·9]), lipase increased (7·2% [5·2–9·9]), and lymphopenia (10·3% [4·5–21·8]). All included randomised controlled trials had a low risk of bias. Interpretation: Our study provides comprehensive data on treatment-related adverse events of different PD-1 or PD-L1 inhibitor-based combination therapies. Our results provide an essential reference of toxicity profiles of PD-1 or PD-L1 inhibitor-based combination therapies for clinicians in routine practice of cancer care. Funding: National Key Research and Development Programme, National Natural Science Foundation of China key program, National Natural Science Foundation of China general program, Chinese Academy of Medical Sciences Initiative for Innovative Medicine, Beijing Municipal Science and Technology Commission, Non-profit Central Research Institute Fund.